2013
DOI: 10.1186/1748-717x-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between radiation pneumonitis and organizing pneumonia after radiotherapy for breast cancer

Abstract: BackgroundRadiation pneumonitis (RP) and organizing pneumonia (OP) are the two main types of lung damage that can occur after lung irradiation. The goal of this study was to evaluate the relationship between RP and OP after irradiation for breast cancer.MethodsFour hundred and twenty-eight patients who underwent radiotherapy for breast cancer were identified. The whole breast was irradiated with two tangential photon beams. Chest computed tomography (CT) scan were performed when patients showed any symptoms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
0
35
1
Order By: Relevance
“…Ten Japanese epidemiological studies were identified [15][16][17][18][19][20][21][22][23][24]. Several studies were from a single institution [16,17,20,21,23,24], and one study was a survey among 20 institutions (Table 1) [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten Japanese epidemiological studies were identified [15][16][17][18][19][20][21][22][23][24]. Several studies were from a single institution [16,17,20,21,23,24], and one study was a survey among 20 institutions (Table 1) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies were from a single institution [16,17,20,21,23,24], and one study was a survey among 20 institutions (Table 1) [18]. These reports described BOOP occurring in 129 of 7,671 women (1.7%), and studies showed a range of prevalence from 0.8% to 2.9% [15][16][17][18][19][20][21][22][23][24]. Five of the 9 reports showed patients received a traditional whole-breast irradiation protocol of 50 Gy in 25 fractions [19][20][21]23, 24], 1 report showed 248 patients received hypofractionated whole-breast radiotherapy [17], 1 report included patients who received whole-breast irradiation or accelerated hyperfractionated whole-breast irradiation [15], and there was no information about the radiation protocol for 3 reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike RP, COP occurs independent of the radiation dose and outside the radiation field. RP typically occurs in the peripherally in the irradiated lung, while COP can occur outside the radiation field [5].…”
Section: Introductionmentioning
confidence: 99%